Factors influencing doctors’ decisions to prescribe antibiotics to inpatients in public hospitals: a qualitative study - Kong, Lai S; Islahudin, Farida; Koh, Kwee C; Muthupalaniappen, Leelavathi; Chong, Wei W (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to understand the factors that influence doctors’ decisions to prescribe antibiotics to inpatients in Malaysian public hospitals and to identify potential targets for quality improvement interventions. Methodology: A qualitative study was conducted from October 2020 to July 2021 using a semi-structured interview technique with doctors in the internal medicine, surgical, and orthopedic departments of 6 public hospitals in Malaysia. Purposive sampling was applied to select doctors with at least 6 months of working experience, and interviews were conducted until data saturation. The interviews were recorded and transcribed verbatim. Thematic analysis was used to analyze data by generating codes and grouping into main themes and subthemes. Results: Twenty-two doctors were recruited for interviews, and 5 interrelated themes were generated. The complex decision-making process for prescribing antibiotics involved intra-personal and socio-cultural context of the hospital settings. The prescriber-related factors affecting decision-making included prescribers’ competency, attitude, and the influence of other prescribers; and patient-related factors included clinical presentation and medical history. Orthopedic and surgical practices frequently considered surgery-related factors and types and sources of infection. Antibiotic-related factors consisting of pharmacokinetic and pharmacodynamic properties were also determinants. Organization setting-related factors included organizational policies, working environment, and resource availability; and these were mainly described by respondents from limited-resource hospitals. Conclusions: This study provides valuable insights into the intrinsic and extrinsic factors and barriers that influence doctors’ decisions to prescribe antibiotics to inpatients in Malaysian public hospitals. These findings should be considered when developing future interventions aimed at improving antibiotic prescribing practices.